Cultural and Religious Authority in Public Health: The Role of Ulema and Traditional Leaders in Stunting Prevention in Kampar Regency, Indonesia - Nur Kholis; Dewi Septiana; Muhammad Nufus Rahmatullah; Muhammad Yusuf (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
Stunting is a global health issue affecting approximately 22% of toddlers worldwide, with a prevalence rate of 21.6% in Indonesia (SSGI 2022), necessitating a multisectoral approach that includes the role of local actors. This study aims to explore the role of religious leaders (ulema) and traditional community leaders in stunting prevention efforts in Kampar Regency, an area facing challenges related to child malnutrition. Stunting, resulting from chronic malnutrition, not only hinders child growth but also diminishes long-term human resource quality. The study examines how these leaders, as social influencers, contribute through educational and advocacy activities. A qualitative method was chosen to gain an in depth understanding of their perspectives, experiences, and community participation dynamics, employing data collection techniques such as in-depth interviews and focus group discussions involving Ulema, traditional leaders, health agency representatives, and local government officials. Data analysis reveals their key role in raising public awareness about balanced nutrition and proper parenting, primarily through religious sermons, Islamic study groups, and traditional rituals. Major challenges include insufficient program integration with the health system and the need for further training. These findings highlight the importance of structured collaboration among local leaders, the health sector, and the government to strengthen holistic stunting prevention efforts.